Market and contractor factors affecting rapid acquisition strategies. Issue 4 (5th April 2021) - Etemadi, Amir; Kamp, John
Abstract: The Department of Defense (DoD) is experimenting with acquisition strategies intended to deliver new capabilities in cycle times of 2 to 5 years. These are executed in a market of few sellers, limited procurement quantities, and constrained budgets. Defense contractors respond by developing, producing, and supporting products. This research analyzed selected publicly‐released acquisition program data from 2007 to 2018.  Quantitative methods identified significant factors and analyzed how acquisition strategy decisions and market conditions are related to these factors. Outcomes important to the government such as shorter cycle times are shown to be statistically associated with early government strategy decisions such as agile software development, and intentional use of commercial technology. Defense contractor responses within this market are related to government programmatic factors and not to reduced cycle times.